Urban green in conservation of biodiversity in João Pessoa, Paraiba, Brazil - Araújo, Yuri Rommel Vieira; Moreira, Zayne Christina Gonçalves (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Urban growth has increasingly altered the natural characteristics of ecosystems in populated areas, resulting in the reduction of natural areas and biodiversity. To minimize the negative impacts of urban sprawl, green areas and protected areas are created. In this context, this study aimed to analyze the importance of urban green in the urban area of João Pessoa, Paraíba, for the conservation of biodiversity in a population cluster. The method consisted of exploratory and explanatory research, with bibliographic survey of public access and field work in green areas, parks, squares, forest remnants, preservation areas and Conservation Units. We identified 85 tree and palm species from 34 different families, seven of which were endangered. Thirty six bird species, nine reptile species and eight mammal species were also identified. An interaction between specific groups of fauna and species of flora was found. The urban green of João Pessoa-PB contributes to the conservation of native flora and endangered species; there are groups of birds, mammals and reptiles using urban green for food, shelter or feeding, and; the municipality has a diversity of relevant species, yet there is a need to create protected areas.